2016
DOI: 10.1093/mnras/stw414
|View full text |Cite
|
Sign up to set email alerts
|

Probing the magnetic field of the nearby galaxy pair Arp 269

Abstract: We present a multiwavelength radio study of the nearby galaxy pair Arp 269 (NGC 4490/85). High sensitivity to extended structures gained by using the merged interferometric and single dish maps allowed us to reveal a previously undiscovered extension of the radio continuum emission. Its direction is significantly different from that of the neutral gas tail, suggesting that different physical processes might be involved in their creation. The population of radio-emitting electrons is generally young, signifying… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…The authors used these observations to find a mean equipartition magnetic field of 21.9 ± 2.9 μG, with typical field strengths in the range of 18-40 μG. Wefound a typical equipartition magnetic field strength of ≈40 μG in the central region, which decreases to ≈17 μG in the outer region (see Figure 2); these values are consistent with the estimates of Nikiel-Wroczynski et al (2016). We find a relatively lower magnetic field strength of ≈15 μG in both the interacting region and the companion galaxy NGC 4485.…”
Section: Details Of the Individual Galaxies Of Samplesupporting
confidence: 76%
“…The authors used these observations to find a mean equipartition magnetic field of 21.9 ± 2.9 μG, with typical field strengths in the range of 18-40 μG. Wefound a typical equipartition magnetic field strength of ≈40 μG in the central region, which decreases to ≈17 μG in the outer region (see Figure 2); these values are consistent with the estimates of Nikiel-Wroczynski et al (2016). We find a relatively lower magnetic field strength of ≈15 μG in both the interacting region and the companion galaxy NGC 4485.…”
Section: Details Of the Individual Galaxies Of Samplesupporting
confidence: 76%
“…Nikiel-Wroczyński et al (2016) published a multi-frequency radio continuum study of this system using archival VLA data and new GMRT observations at 610 MHz. The highest frequency at which NGC 4490/85 has been studied was 25 GHz (Klein 1983).…”
Section: The Galaxiesmentioning
confidence: 99%
“…Radio continuum studies of NGC 4490/85, a closely interacting pair of galaxies, were reported by Viallefond et al (1980, 1.4 GHz), Clemens et al (19992 GHz), and by Klein et al (1983, 24.5 GHz). Nikiel-Wroczyński et al (2016) published a multi-frequency radio continuum study of this system using archival VLA data and new GMRT observations at 610 MHz. The highest frequency at which NGC 4490/85 has been studied was 25 GHz (Klein 1983).…”
Section: The Galaxiesmentioning
confidence: 99%
“…This is a strong magnetic field -stronger than the typical ones found for spiral galaxies by Niklas (1995), and approximately two times stronger than the one derived for the radio-emitting TDGc SQ-A and SQ-B (Nikiel-Wroczyński et al 2013b). Such a strength is similar to that of the compact disk areas of star formation: Beck & Wielebinski (2013) lists several objects that host even stronger magnetic fields, and the study of the magnetic field of starburst dwarf spiral galaxy NGC 4490 (Nikiel-Wroczyński et al 2016) reveals a handful of disk starburst regions hosting magnetic fields exceeding 20 µG in strength. Compared to the other dwarf galaxies, HCG 91i seems to posses a magnetic field similar to that of the starburst dwarf galaxies studied by Chyży et al (2011).…”
Section: Magnetic Field Inside the Tdg Candidatesmentioning
confidence: 78%
“…Young supernovae remnants have in general much flatter indices: the lower limit is assumed to be equal to 0.3 (Weiler & Sramek 1988). Such flat spectra are indeed seen in case of disk star forming regions -like it happens in case of the dwarf starburst galaxy pair Arp 269 (Nikiel-Wroczyński et al 2016). A rough estimate of the spectral age, made under the assumption that the break frequency of the spectrum is already below 4.86 GHz suggests that the radio emission must be older than approximately 10-15 Myrs -likely more.…”
Section: An Inherited Magnetic Field?mentioning
confidence: 99%